Bilateral alloplastic temporomandibular joint reconstruction with orthognathic surgery: a case report of idiopathic condylar resorption - Alali, Yasser S.; Habeeb, Khaled M. Al; Malhook , Khaled A. Al (International Journal Of Community Medicine And Public Health, 2024)
Idiopathic condylar resorption (ICR) also known as cheerleader’s syndrome, progressive condylar resorption, idiopathic condylysis, and condylar atrophy can be defined as chronic ongoing changes of condylar shape and decrease in mass. It is characterized by an excessive physical stress to the articular structures of the temporomandibular joint (TMJ) that exceeds the normal adaptive capacity. Consequently, leading to decrease condylar head volume, decrease ramus height, progressive mandibular retrusion in adults, or decreased growth rate in adolescents. A case report of a 30-year-old female based on the history, clinical, and radiographic examination has class II skeletal relationship secondary to bilateral ICR, receded chin, vertical maxillary excess (VME) and canting. Surgical treatment plan was established using 3D Systems, Inc., (“3DS”) VSP® and case was managed by bilateral total alloplastic temporomandibular joint reconstruction (BATMJR) with orthognathic surgery to do LeFort I, bilateral condylectomy, genioplasty, and inferior border osteotomy. The case report includes one-year follow-up which shows stable outcome, emphasizing long-term success of comprehensive treatment strategy in addressing skeletal class II malocclusion associated with ICR.